Psychosocial interventions - Burns, T (1997)
Research into psychosocial management in schizophrenia is witnessing a new phase in family approaches with studies sufficiently differentiated to permit distinction of the effective ingredients and yet sufficiently similar to allow for meta-analysis. Individual patient work has begun to benefit from cognitive behaviour therapy approaches and the centrality of medication compliance is increasingly clear. The challenge is to devise and research interventions sustainable in routine practice.